High‐dimensional flow cytometry reveals lymphocyte subset populations predictive of chronic lung allograft dysfunction - Rohia Farighi; Steven Hiho; Thomas Ashhurst; Emily SJ Edwards; Lucy Sullivan; Menno C vanZelm; Greg Snell; Glen Westall; David M Tarlinton; Dimitra Zotos (Clinical & Translational Immunology, 2025)
Abstract Objectives Despite cellular and antibody‐mediated rejection being clinically relevant drivers of chronic lung allograft dysfunction (CLAD), there are few studies describing the T‐ and B‐cell dynamics inherent to such alloreactive responses. We conducted a longitudinal immunophenotyping study of B‐ and T‐cell subsets from pre‐ to 12 months post‐lung transplant, focussing on patients who subsequently developed either donor specific antibodies to human leukocyte antigen class II (HLA‐DSA) or CLAD within 3 years. Methods In a single centre, comparative study, we used high‐dimensional flow cytometry clustering analysis to assess the B‐ and T‐cell populations in blood from lung allograft recipients prior to transplantation and at 0.5, 1.5, 3, 6, 9 and 12 months post‐transplantation. Recipients who developed de novo HLA‐DSA at 3 months post‐transplantation (n = 18) and those in whom CLAD was diagnosed within 3 years post‐transplantation (n = 13) were compared to matched, DSA‐negative (n = 15) or CLAD‐free recipients (n = 26), respectively. Results This longitudinal study provided a detailed analysis of B‐ and T‐cell lineage subsets, including both cell frequencies and cell counts. There were no statistically significant differences in lymphocyte populations between graft recipients with and without HLA‐DSA. However, patients that developed CLAD had a mean threefold deficit in the absolute number of B cells and had significantly fewer T regulatory cells than CLAD‐free patients. Strikingly, these differences existed prior to and persisted post‐transplantation. Conclusions Utilising high‐dimensional flow cytometry, a new putative association was identified between two peripheral blood lymphocyte populations and the subsequent development of CLAD.